Bioinformatic determination of the contamination in environmental DNA from water - Höller, Max (Jihočeská univerzita, 2023)
The aim of the study is to analyse raw sequences gained during the collection of environmental DNA from water. The samples were collected from different water environments during different seasons. The used vertebrate-specific primers amplify not only fish but other vertebrates and bacteria. The ratio and diversity of the groups detected in different campaigns are important for stakeholders for efficient utilisation of the method for biodiversity monitoring.
Bioinformatic determination of the contamination in environmental DNA from water
Keywords: eDNA; Metabarcoding; fish; conservation; species distribution; species detection; biodiversity monitoring; eDNA; Metabarcoding; fish; conservation; species distribution; species detection; biodiversity monitoring